Effect of hypoxia conditioning on physical fitness in middle-aged and older adults—a systematic review and meta-analysis - Fanji Qiu; Jinfeng Li; Liaoyan Gan (PeerJ)
Background Hypoxic conditioning has emerged as a promising intervention for enhancing physiological adaptations. This systematic review and meta-analysis of randomized controlled trials aims to investigate the efficacy of hypoxic conditioning on physical fitness measures in aging populations. Methods The Embase, PubMed, Cochrane Library, and Web of Science were searched from inception to November 2024 (Prospero registration: CRD42023474570). The Cochrane Evaluation Tool and Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework were used for risk of bias assessment and evidence certainty evaluation. Mean differences (MD) and standardized mean differences (SMD) and 95% confidence intervals (CI) were calculated using the Review Manager software. Subgroup analysis was performed to explore possible associations between the study characteristics and the effectiveness of the intervention. Results A total of 13 randomized controlled trials (RCTs) with 368 subjects were included in the meta-analysis. High certainty evidence found hypoxic conditioning (HC) significantly improved peak oxygen uptake (VO2peak) (SMD = 0.31, 95% CI [0.01–0.61]; P < 0.05), while very low to moderate certainty evidence shown that hypoxic conditioning (HC) have not induced greater changes on functional outcomes (SMD = −0.21, 95% CI [−0.66–0.24]; P > 0.05), muscle strength (SMD = −0.19, 95% CI [−0.63–0.26]; P > 0.05), maximal power output (SMD = 0.29, 95% CI [−0.17–0.76]; P > 0.05), VO2max (SMD = −0.39, 95% CI [−1.12–1.90]; P > 0.05), and exercise workload (MD = −10.07, 95% CI [−34.95–14.80]; P > 0.05). Conclusion This study suggests that hypoxia conditioning has a greater effect on enhancing VO2peak compared to equivalent normoxic training in the middle-aged and older population. More high-quality RCTs are needed in the future to explore the optimal oxygen concentration and exercise intensity during hypoxia conditioning.